International Conference "Armenia-Iran. Historical Past and the Present" - Gohar Iskandaryan (Banber Arevelagitut'yan Instituti)
"Armenia-Iran. The Historical Past and Present" international conference took place in the conference hall of the Presidium of the National Academy of Sciences of the Republic of Armenia (NAS RA) on February 9-10, 2022. The conference was dedicated to the 30th anniversary of the establishment of diplomatic relations between the Republic of Armenia and the Islamic Republic of Iran (IRI).